A scoping review on the prevalence of Shiga‐toxigenic Escherichia coli in wild animal species. (11th August 2018) - Espinosa, Laura; Gray, Aimée; Duffy, Geraldine; Fanning, Séamus; McMahon, Barry J.
Abstract: Zoonotic pathogens constitute the major source (60.3%) of emerging infectious diseases. Previous studies have investigated the prevalence of Shiga‐toxigenic Escherichia coli (STEC) among wild animal species, but comprehensive data are needed to assess the role that these animals have in the transmission of STEC infections to the human population via faecal contamination of the environment, agri‐food or water chain. Due to the nature of these microorganisms in which this human–animal–environment interface plays a relevant role on the disease's dynamics, a "One Health" approach is needed to prevent and control the worldwide spread. The aim of this study was to review the published research on the prevalence of STEC in wildlife. The search was performed using several online databases consisting of three blocks of specific search terms covering pathogen, type of study and population. Two reviewers applied the inclusion and exclusion criteria to screening and eligibility phases. Two hundred and twenty‐five abstracts were screened for relevance, and 72 were included for data analysis. Most studies (77.8%) investigated the prevalence of STEC in ruminants and urban birds. Their role in transmitting the pathogen to humans, other animals and the agri‐food chain is potentiated by the peculiar biological characteristics in ruminants and improved adaptation of urban birds to urban environments. The popularity of convenience and voluntary response sampling may be due to the lack of human‐made boundaries on the wild animal species' habitat and having some samples from hunted‐harvested animals. To our knowledge, this is the first comprehensive review on STEC prevalence in wild animal species from studies conducted across the globe. We recommend that future research includes and compares samples from varying origins (i.e., human, animal, environment and food) and applies a "One Health" approach to the emerging challenges that STEC poses to public health.